Decisions of the Comptroller General of the United States (G.P.O. : For sale by the Supt. of Docs., 1922)
Contains a selection of major decisions of the GAO. A digest of all decisions has been issued since Oct. 1989 as: United States. General Accounting Office. Digests of decisions of the Comptroller General of the United States. Before Oct. 1989, digests of unpublished decisions were issued with various titles.